Prison life writing: conversion and the literary roots of the U.S. prison system - Rolston, Simon (Life writing series, 2021)
"The first full-length study of prison life writing, this book shows how the autobiographical literature of incarcerated people is consistently based on a conversion narrative, the same narrative that underpins prison rehabilitation. By demonstrating how prison life writing interlocks with institutional power, the book challenges conventional preconceptions about writing behind bars. And yet, imprisoned people often use the conversion narrative like they repurpose other objects in prison: much like the radio motor retooled into a tattoo gun, the conversion narrative is often redefined to serve subversive purposes like questioning the supposed emancipatory role of prison writing, critiquing white supremacy, and reconfiguring what can be said in autobiographical discourse. An interdisciplinary work that brings life writing scholarship into conversation with prison studies and law and literature studies, Prison Life Writing theorizes how life writing works in prison, explains literature’s complicated entanglements with institutional power, and demonstrates the political and aesthetic innovations of one of America’s most controversial literary genres."--